Analisis Maqāṣid al-Syarī’ah terhadap Peraturan Pemerintah (PP) Nomor 25 Tahun 2024 Tentang Pemberian Izin kepada Ormas Keagamaan untuk Mengelolah Tambang: Analysis of Maqāṣid al-Syarī’ah Regarding Government Regulation (PP) Number 25 of 2024 Concerning the Granting of Permits to Religious Organizations to Manage Mines - Iskandar, Iskandar; Jamaluddin, Jamaluddin; Muh. Afif Fadhil (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
Indonesia is one of the countries with the most abundant natural resources. These resources include coal and minerals. However, their management often causes environmental damage and social inequality. One of the latest policies, Government Regulation No. 25 of 2024, grants religious community organizations permission to manage mines. This policy has sparked pros and cons, making it interesting to examine from the perspective of Maqāṣid al-Syarī‘ah, which emphasizes benefit and the prevention of damage. From this background, the author can raise the following research questions: First, what are the provisions contained in Government Regulation No. 25 of 2024 concerning the Granting of Mining Management Permits to Religious Organizations? Second, what is the view of Maqāṣid al-Syarī‘ah on this regulation? The type of research used in writing this thesis is library research, namely written research from various references conducted by collecting data, examining and analyzing data from various literature, analyzing theories, concepts, legal principles, rules, and regulations related to this research. The objective is to explain the perspective of maqasid syariah on the granting of mining management permits to religious organizations. The results of this study show that, first, based on the provisions of Article 6 paragraph (1) letter j of Law 3/2020, which explains that the central government is tasked with managing mineral mining and has the authority to prioritize WIUPK offers as the basis for granting mining business licenses to religious organizations, in accordance with the Explanation of Article 83A paragraph (1) of PP 25/2024. Second, based on the view of Maqāṣid al-Syarī‘ah, this regulation has a greater and more obvious mafsadah mu’tabarah (harm) than its potential maṣlaḥah (benefit).